1998
DOI: 10.1161/01.hyp.32.3.410
|View full text |Cite
|
Sign up to set email alerts
|

Calcium Channel Blockade and Cardiovascular Prognosis in the European Trial on Isolated Systolic Hypertension

Abstract: Abstract-In the double-blind Systolic Hypertension in Europe (Syst-Eur) Trial, active treatment was initiated with nitrendipine (10 to 40 mg/d) with the possible addition of enalapril (5 to 20 mg/d) and/or hydrochlorothiazide (12.5 to 25 mg/d) titrated or combined to reduce sitting systolic blood pressure by at least 20 mm Hg to Ͻ150 mm Hg. In the control group, matching placebos were used similarly. (nϭ2297), patients receiving monotherapy with nitrendipine had 25% (Pϭ0.05) fewer cardiovascular end points, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
21
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(26 citation statements)
references
References 18 publications
3
21
0
2
Order By: Relevance
“…Benefit was also noticed in patients who remained on monotherapy with active nitrendipine. 20 Nitrendipine-based treatment was particularly effective in diabetic patients, in whom active treatment was estimated to prevent 178 severe cardiovascular complications as opposed to only 22 in the non-diabetic group. 21 The per-protocol analysis 12 considered only the end-points which had occurred during double-blind treatment and confirmed the results by intention-totreat.…”
mentioning
confidence: 99%
“…Benefit was also noticed in patients who remained on monotherapy with active nitrendipine. 20 Nitrendipine-based treatment was particularly effective in diabetic patients, in whom active treatment was estimated to prevent 178 severe cardiovascular complications as opposed to only 22 in the non-diabetic group. 21 The per-protocol analysis 12 considered only the end-points which had occurred during double-blind treatment and confirmed the results by intention-totreat.…”
mentioning
confidence: 99%
“…Active treatment reduced total mortality (P = 0.04), cardiovascular mortality (P = 0.02) and all cardiovascular endpoints (P = 0.01) significantly more in the diabetic than the non-diabetic Syst-Eur patients. 29 In spite of the evidence produced by the Syst-Eur trial 3,9,27,29 and other placebo-controlled outcome studies in hypertension, 10,11 the controversy about the use of calcium-channel blockers as first-line drugs for the treatment of hypertension is still alive. Several arguments fuel the debate.…”
Section: Discussionmentioning
confidence: 99%
“…3 Cardiovascular benefit was equally observed in the patients remaining on monotherapy with nitrendipine as in those pro-gressing to combined treatment with nitrendipine plus enalapril, hydrochlorothiazide, or both drugs. 9 At the risk observed in the placebo group (intentionto-treat analysis), treating 1000 patients for 5 years could prevent 29 strokes or 53 major cardiovascular events. 3 Similar findings were obtained in two placebo-controlled trials in China, in which antihypertensive treatment was also started with a dihydropyridine.…”
Section: Rationale and Objective Of Syst-eurmentioning
confidence: 99%
See 1 more Smart Citation
“…8 Staessen et al 11 showed the usefulness of treatment with calcium antagonist monotherapy in the Syst-Eur study reanalysis. These studies used twice-daily long-acting calcium antagonists and demonstrated that calcium antagonists and diuretic treatment have a similar preventive effect against cardiovascular events; there was greater protection against stroke than against myocardial infarction.…”
Section: Nics-eh Study Group Calcium Antagonist and Diuretic In The Ementioning
confidence: 99%